2021
DOI: 10.3892/br.2021.1436
|View full text |Cite
|
Sign up to set email alerts
|

The role of HPV‑induced epigenetic changes in cervical carcinogenesis (Review)

Abstract: Cervical cancer is associated with infection by certain types of human papillomaviruses (HPVs), and this affects women worldwide. Despite the improvements in prevention and cure of HPV-induced cervical cancer, it remains the second most common type of cancer in women in the least developed regions of the world. Epigenetic modifications are stable long-term changes that occur in the DNA, and are part of a natural evolutionary process of necessary adaptations to the environment. They do not result in changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 154 publications
0
22
0
Order By: Relevance
“…Since hyper-methylation of the promoters of regulatory genes is known to result in activation of oncogenes and inactivation of tumor suppressor genes, proportion of hyper-methylated genes tends to be higher in cancerous tissue compared to healthy tissues from the same anatomical site. This has been observed in both HPV-associated cancers, e.g., cervical SCC, and in HPV-independent cancers, e.g., oral and laryngeal SCC [ 45 , 46 ]. Studies on cervical SCC indicate that the HPV-oncoproteins E6 and E7 activate DNA methyltransferases, which promote the hyper-methylation of CpG-islands and silencing of host genes, including CDH1 , TP53 , RASSF1, and CDKN2A [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since hyper-methylation of the promoters of regulatory genes is known to result in activation of oncogenes and inactivation of tumor suppressor genes, proportion of hyper-methylated genes tends to be higher in cancerous tissue compared to healthy tissues from the same anatomical site. This has been observed in both HPV-associated cancers, e.g., cervical SCC, and in HPV-independent cancers, e.g., oral and laryngeal SCC [ 45 , 46 ]. Studies on cervical SCC indicate that the HPV-oncoproteins E6 and E7 activate DNA methyltransferases, which promote the hyper-methylation of CpG-islands and silencing of host genes, including CDH1 , TP53 , RASSF1, and CDKN2A [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed in both HPV-associated cancers, e.g., cervical SCC, and in HPV-independent cancers, e.g., oral and laryngeal SCC [ 45 , 46 ]. Studies on cervical SCC indicate that the HPV-oncoproteins E6 and E7 activate DNA methyltransferases, which promote the hyper-methylation of CpG-islands and silencing of host genes, including CDH1 , TP53 , RASSF1, and CDKN2A [ 45 ]. It could be investigated whether the HPV-oncoproteins cause gene silencing in HPV-associated VSCCs using a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Methylome analyses of HPV-positive cancers revealed differences in DNA methylation compared to matching normal tissue or HPV-negative tumors and transfection studies have confirmed that the E6 and E7 oncoproteins provoked hypermethylation tumor suppressor genes and hypomethylation of proto-oncogenes [ 31 , 32 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ]. Both these viral proteins have been shown to upregulate the expression of DNMT1.…”
Section: Oncoviruses and Host Cell Dna Methylationmentioning
confidence: 99%
“…The mechanism(s) by which HR-HPV provoke hypomethylation of the host genome remain enigmatic. In conclusion, HPV-mediated changes in DNA methylation affects the expression of several cellular genes and has been proven to stimulate cell proliferation, cell survival, adhesion and migration [ 32 , 114 ].…”
Section: Oncoviruses and Host Cell Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation